User Modeling, Adaptation and Personalization 22nd International Conference, UMAP 2014, Aalborg, Denmark, July 7-11, 2014. Proceedings - Dimitrova, Vania; Kuflik, Tsvi; Chin, David; Ricci, Francesco; Dolog, Peter; Houben, Geert-Jan (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This book constitutes the thoroughly refereed proceedings of the 22nd International Conference on User Modeling, Adaption and Personalization, held in Aalborg, Denmark, in July 2014. The 23 long and 19 short papers of the research paper track were carefully reviewed and selected from 146 submissions. The papers cover the following topics: large scale personalization, adaptation and recommendation; Personalization for individuals, groups and populations; modeling individuals, groups and communities; Web dynamics and personalization; adaptive web-based systems; context awareness; social recommendations; user experience; user awareness and control; Affective aspects; UMAP underpinning by psychology models; privacy; perceived security and trust; behavior change and persuasion.